Pay Transparency Under Subjective Performance Evaluation - Matthias Fahn; Giorgio Zanarone (Center for Economic Studies and Ifo Institute (CESifo), 2021)
This paper studies how pay transparency affects organizations that reward employees based on their efforts (i.e., using “subjective performance evaluation”). First, we show that transparency triggers social comparisons that require the organization to pay its employees an “envy premium”. This premium reduces the value of the employment relationship to the organization, and thus its incentive to pay subjective bonuses to the hard-working employees. To restore credibility of its incentive system, a transparent organization must therefore reduce the weight of bonuses, and increase the weight of fixed salaries, in the employees' compensation, relative to organizations that operate in a more conventional “pay secrecy” regime. Second, we show that transparency enables the employees to collectively sanction the organization for reneging on subjective incentives. Collective enforcement allows the transparent organization to use strong employment relationships to “cross-subsidize” weak ones, achieving a more balanced allocation of effort than under pay secrecy. We discuss testable implications of our model for compensation design, the choice between transparency and secrecy regimes, and organizational responses to pay transparency laws.
Keywords: D03; D23; M52; M54; 330; social comparisons; secrecy; transparency; relational contracts; incentives